2000
DOI: 10.1046/j.1440-1614.2000.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards people with depression: effects on the public's help-seeking and outcome when experiencing common psychiatric symptoms

Abstract: The attitude measures did not predict patterns of help-seeking or outcome for people with common psychiatric symptoms. However, attitudes towards depression were quite benign and the situation could be different for people with severe mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 14 publications
2
44
2
1
Order By: Relevance
“…However, in an analysis of other data from this study, we found that attitude measures about depression did not predict help-seeking [15]. The interventions that were ranked more highly for likely helpfulness than for actual use mainly involved the services of mental health professionals.…”
Section: Table 2 Predictors Of Using Various Interventions To 'Cope contrasting
confidence: 69%
“…However, in an analysis of other data from this study, we found that attitude measures about depression did not predict help-seeking [15]. The interventions that were ranked more highly for likely helpfulness than for actual use mainly involved the services of mental health professionals.…”
Section: Table 2 Predictors Of Using Various Interventions To 'Cope contrasting
confidence: 69%
“…However, findings are mixed regarding the impact of public stigma on actual treatment seeking , with the majority of the reports supporting public stigma as a barrier (Aromaa, Tolvanen, Tuulari, & Wahlbeck, 2011; Cooper, Corrigan, & Watson, 2003; Nadeem et al, 2007; Schomerus, Matschinger, & Angermeyer, 2009) whereas contrary findings have also been observed (Jorm et al, 2000; Ng et al, 2008). Regarding the role of perceived public stigma towards mental illness, we did not find support in the extant literature for significant relationship between this type of stigma and either willingness to seek treatment (Brown et al, 2010; Golberstein, Eisenberg, & Gollust, 2008; Schomerus et al, 2009), or treatment seeking/involvement (Brown et al, 2010; Golberstein et al, 2008; Komiti, Judd, & Jackson, 2006; Rüsch et al, 2009).…”
Section: Help Seeking Stigma and Mental Health Treatment Seeking Amonmentioning
confidence: 95%
“…Up to half of those who fail to complete secondary school have mental illness [10]. Those who do, more often turn to friends and family for help than to health professionals [11,12]. Teenagers seek help less often than adults [13].…”
Section: Introductionmentioning
confidence: 99%